Challenges Confronting the Administration of English Language Program: Secondary School Context in Nigeria - Ogunode, Niyi Jacob (REiLA : Journal of Research and Innovation in Language, 2020)
This objective of this study was to investigate the challenges facing the administration of English Language program in Senior Secondary schools in Abaji Area Council of Federal Capital Territory (FCT), Nigeria. The study used questionnaire as instrument for data collection. 80 respondents were selected from the entire population of English teachers and school administrators in Abaji. Purposive research techniques were employed to select the respondents. Research survey method was adopted for the study. To determine the reliability of the instrument, test and retest methods. The data collected were analysed using simple percentage, mean statistical and chi-square was employed to test the hypotheses. The result collected from the study led to the following conclusion that scant fund, shortage of professional English teacher, inadequate English language instructional materials, deficient English laboratory, poor capacity development of English language teachers and paltry motivation of English language teacher are the challenges affecting the effective administration of English language program in Abaji secondary Schools.